What Can MENA Governments Expect in 2016? - Mottaghi, Lili (World Bank, Washington, DC, 2016)
This year will be the fifth consecutive year with global growth below its long-term trend of 3.5% observed during 2000-07, standing at last year’s 2.4%. This is 0.5% below January’s forecast. Many countries are plagued by recession, several others suffer from terrorist attacks and refugee crises, while some are mired in civil wars together with extremely uncertain commodity markets, especially oil. The result has been lower potential output and investment, and weaker global demand. In advanced economies, real growth remained uncomfortably low, almost 1% below the long term average from 2000 to 2007.